Storify : Protecting privacy of social media post with hash-based anonymity - Jackie Chin Yong An (2022)
In year 2020, the number of users using social networking has exceeded 3.6 billions out of 7.6 billions people, which is 47% of the populations. There are some famous social media applications that are widely used worldwide, which are Facebook, Twitter, Snapchat and many more. However, social media has some negative effect which has been labelled as a “likely culprit” that leads youngsters to depression, social isolation and have suicidal thoughts. Lack of anonymous features of recent social media apps that allow users to express their feelings without getting hurt by cyber bullying has urged recently to protect user’s privacy. This project proposes a social media application, called as “Storify”, that aimed to protect privacy of social media post with hash-based Anonymity. The objectives of this project are to investigate a lightweight hash-based anonymity algorithm in protecting the privacy of social media post, in terms of computation speed and ciphertext size, to design and develop the proposed Storify mobile social media application by using prototype development approach and to evaluate the performance of the developed Storify mobile social media application by using System Usability Scale (SUS) approach. Questionnaire and quantitative survey is used to gather user requirements. The hash-based algorithm is conducted through testing. The outcome of this proposed project is to confirm the lightweight hash-based anonymity algorithm with the fastest computation speed and greater ciphertext size.